PENINGKATAN KETERAMPILAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN ORIGAMI DI TK PENGEMBANGAN 21 TACIM KAB. HALMAHERA BARAT - Diana Salim; Rita Samad (EDUKASI, 2020)
This study aims at investigating the increases of children’s ages 5-6 years gross motor skills through origami activities at TK Pengembangan 21 Tacim, West Halmahera. This study is a Classroom Action Research (collaborative) which consists of two cycles in four meetings. The researcher acts as a teacher who runs the learning scenario while collaborator is a teacher assistant who act as observers (observers). The subjects of the study were 8 children of Class B Pengembangan Kindergarten 21 Tacim Kab. Halbar, they consist of 4 Male and 4 Female. Technique collecting data are observation and field notes. The instrument of research is observation sheets in the form of a checklist of children fine motor skills. The data were analyzed qualitative descriptive. The results of this study indicate that an increase in children's fine motor skills through origami activities in TK Tac 21 Pengembangan. Improvement of children gross motor skills in cycle I is 50% or 4 children of 8 children that were categozied very good and good in shapeing the paper neatly based on the shape of object. The result of cycle II indicates that 88% of children or 7 children of 8 children were categorized very good and good in shaping the paper quickly and neatly according to the shape of the object. Thus, origami activities can improve fine motor skills of children aged 5-6 years in TK Pengembangn 21 Tacim, West Halmahera.